Substance Abuse, Relapse, and Treatment Program Evaluation in Malaysia: Perspective of Rehab Patients and Staff Using the Mixed Method Approach - Chie, Qiu Ting; Tam, Cai Lian; Bonn, Gregory; Dang, Hoang Minh; Khairuddin, Rozainee (Frontiers in Psychiatry, 2016)
This study examined reasons for substance abuse and evaluated the effectiveness of substance treatment programs in Malaysia through interviews with rehab patients and staff. Substance rehab patients (aged 18-69 years; n=30) and staff (ages 30-72 years; n=10) participated in semi-structured interviews covering a range of topics including: family and peer relationships, substance use and treatment history, factors for substance use and relapse, motivation for entering treatment, work experience, job satisfaction, treatment evaluation and patient satisfaction. Most patients did not demonstrate the substance progression trend and had normal family relationships. Most patients reported having peers from normal family backgrounds as well. A variety of environmental and personal factors was cited as contributing to substance abuse and relapse. There was no significant difference between patient and staff program evaluation scores although the mean score for patients were lower. A holistic treatment approach with a combination of cognitive-behavioral, medical, social and spiritual components was favored by patients. Suggestions for improving existing programs include better tailoring treatment to individual needs, and providing more post-treatment group support.